Gender and pair programming–Effects of the gender composition of pairs on collaboration in a robotics workshop - Küng, Janine; Schmid, Andrea M.; Brovelli, Dorothee (Frontiers in Education, 2022)
The goal of this video study was to investigate whether the gender composition of a pair influences collaboration during the pair programming process. Pair programming is an agile software development technique in which two people share a computer and jointly develop a program. One of the programmers, the driver, operates the keyboard and mouse; the other, the navigator, reviews the code and helps without touching the keyboard or mouse. These two roles are swapped at regular intervals. Video data were collected during a half-day robotics workshop for students in Grades 5–9 (10–14 years old) and gifted students in Grades 3–6 (8–11 years old) at the University of Teacher Education Lucerne. A total of 203 pairs with different gender compositions (homogeneous female, homogeneous male, heterogeneous) were filmed during the pair programming process. Without consideration of the grade level the research results showed that there were no significant differences between the pairs based on gender composition in terms of task-solving speed, number of assistance requests, role changes, or rule violations by the navigator. In heterogeneous pairs, male and female students in the navigator role intervened equally often. These results initially appear to be consistent with several previous studies, which also found no significant differences based on gender composition. However, when only students in Grades 7–9 (12–14 years old) were considered, there were two significant differences. First, the homogeneous male pairs violated the rule that the navigator does not touch the keyboard or mouse more often than the other pairs. This suggests that homogeneous male pairs are not ideal for students in Grades 7–9 (12–14 years old). Second, as previously shown in other studies, heterogeneous pairs showed the greatest variability in task-solving speed. This may indicate compatibility issues among some heterogeneous pairs in Grades 7–9. In this study, only quantitatively measurable indicators of collaboration were considered. Further research on gender and pair programming should therefore focus on the quality of collaboration.